New Characterization of D- Focal Curves in Minkowski 3-space - Korpinar, Talat; Bas, Selcuk; Asil, Vedat (Soc Paranaense Matematica, 2020)
In this paper, we study new D-focal curves in the Minkowski 3-space with Darboux frame. Moreover, we obtain some integral equations which they are characterizations for a space curve to be a D-focal curve. Finally, we give some characterizations about D-focal curves in the Minkowski 3-space M-1(3).
Keywords: Darboux frame; Minkowski 3-space; Focal curve; Normal curvature; Geodesic Curvature; Geodesic torsion